De l’art délicat des interventions architecturales sur le patrimoine théâtral - Stéphane Millet (In Situ)
A book recently published by AAM is devoted to the architectural firm of Clé Millet Architects and its recent work on the Marigny Theatre. Stéphane Millet gives details on the difficulties inherent in such restoration projects. First of all, in collaboration with the regional cultural services (Direction régionale des Affaires culturelles), an analysis of the existing situation is the delicate prelude, distinguishing between intangible heritage aspects and elements that can be changed. This is followed by the elaboration of solutions which can reconcile the safekeeping of the architecture and its decoration in all its integrity both with the simple stability of the building and with regulatory requirements that are in constant evolution concerning structure, thermal comfort, security and scenography. The Marigny Theatre is an institution open to the public with historic monument protection, and the mission to safeguard it is what is described in this article. The rehabilitation and extension of the theatre accumulated technical challenges associated with the traditional structures designed by Charles Garnier and with materials newly added in contemporary and prospective perspectives.